The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3791/53752
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Specificity of Anticancer Drugs <em>In Vitro</em>

Lan Kluwe

Abstract: A procedure for assessing specificity of anticancer drugs in vitro using cultures containing both tumor and non-tumor cells is demonstrated. The key element is the quantitative determination of a tumor-specific genetic alteration in relation to a universal sequence using a dual-probe digital PCR assay and the subsequent calculation of the proportion of tumor cells. The assay is carried out on a culture containing tumor cells of an established line and spiked-in non-tumor cells. The mixed culture is treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The results revealed that both peptides alone did not significantly affect the survival of DLD-1 cells, whereas individual conjugation to NPs caused an improved and dose-dependent cytotoxic response [ 42 ]. According to Kluwe, L. [ 43 ], tumor cell culture and non-tumor ones provide a potential resource in vitro to assess the specificity or selectivity of a given compound, which may clarify its clinical toxicity. Although some of the aforementioned works describe the cell type as an important factor in the NPs’ cell internalization process, few of them compared the NP internalization in the different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that both peptides alone did not significantly affect the survival of DLD-1 cells, whereas individual conjugation to NPs caused an improved and dose-dependent cytotoxic response [ 42 ]. According to Kluwe, L. [ 43 ], tumor cell culture and non-tumor ones provide a potential resource in vitro to assess the specificity or selectivity of a given compound, which may clarify its clinical toxicity. Although some of the aforementioned works describe the cell type as an important factor in the NPs’ cell internalization process, few of them compared the NP internalization in the different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Because RPP30 is stably expressed in the vast majority of tumor cells and non-tumor cells, while the neurofibromatosis type 1 (NF1) gene loses heterozygosity in tumor cells, the number of tumor cells may be evaluated by the quantitative RT-PCR ratio of NF1 to RPP30, which may be used to evaluate the efficacy and side effects of tumor drugs, and may also be used in personalized adjuvant chemotherapy. Due to the different behavior of cells in vivo and in vitro, this method has some limitations (76)(77)(78). As an internal reference gene, RPP30 may also accurately and effectively evaluate the concentration of antiretroviral drugs in cells (79).…”
Section: Application Of Rpp30 As An Internal Reference Genementioning
confidence: 99%
“…Previously, we demonstrated the feasibility of using a tumor-specific allele loss for determining the proportion of tumor cells in a mixed culture (5,6). The present study aims to further explore the feasibility of using the BRAF mutation c.1799T>A to determine the proportion of tumor over nontumor cells in a mixed culture.…”
mentioning
confidence: 94%
“…A strategy for determining the proportion of tumor cells in a mixed culture is therefore highly desirable. One possible strategy is to quantify a tumor-specific genetic alteration such as a mutation or an allele loss (5,6). For melanomas with the BRAF mutation c.1799T>A, the ratio of the mutant 1799A allele to the wild-type 1799T allele should, at least in theory, enable the calculation of the proportion of the tumor cells in a mixed culture containing both tumor and non-tumor cells.…”
mentioning
confidence: 99%